Diversifiering i lantbruksföretag : en litteraturstudie om hur utvecklingsprocessen ser ut i lantbruksbaserade företag som utvecklar nya verksamhetsgrenar - Romar, Markus (SLU/Dept. of Economics, 2011)
Today´s debate in farming is being focused on tourism, outdoor life and hobbies in the rural areas. This is of interest also for the general public as a way of counteracting the depopulation of the rural areas. Within the last years, the farming has become more technically advanced and hence efficient. This has led to increased production volumes and wider selection of products with lower margins for the farmer as a consequence. When the profitability is reduced, the farmer is faced with the choice of either increasing efficiency or diversification of the business.